PERLINDUNGAN HUKUM TERHADAP NASABAH PENGGUNA LAYANAN PINJAMAN ONLINE ILEGAL MENURUT PERATURAN OJK No.77/POJK.01/2016 TENTANG LAYANAN PINJAM MEMINJAM UANG BERBASIS TEKNOLOGI INFORMASI - Candra Wiwit Muliani (Fakultas Hukum Universitas Islam Malang, 2022)
ABSTRACTThis study aims to analyze the role of the Financial Services Authority in supervising and overcoming illegal online loans and legal protection for customers who use illegal online loan services according to POJK regulations No.77/POJK.01/2016. Progress in finance today is with the existence of Fintech as well as online loans. The emergence of online loans in Indonesia, which is often a problem, is that there are many online loans that are still illegal and do not have an operating permit from the Financial Services Authority. Whereas the number of illegal online loans, the government in this case has the authority, the Financial Services Authority has taken various ways to protect the community, but the problems faced by the community are still happening. The method used in this research is normative juridical using a statutory approach and a conceptual approach. The role of the Financial Services Authority is still very limited because the regulations used, namely POJK No.77/POJK.01/2016 cannot cover all problems that arise, so the Authority Financial Services cannot directly supervise and regulate illegal online loans. Legal protection for customers using illegal online loans according to POJK regulation No.77/POJK.01/2016 in its implementation does not regulate legal protection for illegal online loan customers, until now there is no regulation that regulates legal protection for illegal and legal online loan customers. in particular.Keywords: Illegal Online Loans, Legal Protection, Financial Services Authority. ABSTRAKPenelitian ini bertujuan untuk menganalisis mengenai peran Otoritas Jasa Keuangaan dalam mengawasi dan mengatasi pinjaman online ilegal dan perlindungan hukum terhadap nasabah pengguna layanan pinjaman online ilegal menurut peraturan POJK No.77/POJK.01/2016. Munculnya pinjaman online di Indonesia ini yang sering menjadi permasalahan adalah banyak bermunculan pinjaman online yang masih ilegal tidak mempunyai izin beroperasi dari Otoritas Jasa Keuangan. Metode yang digunakan dalam penellitian ini adalah yuridis normatif dengan menggunakan pendekatan perundang undangan dan pendekatan konseptual. Peran Otoritas Jasa Keuangaan masih sangat terbatas dikarenakan peraturan yang digunakan yaitu POJK No.77/POJK.01/2016 tidak dapat mengcover semua permasalahan yang muncul, sehingga Otoritas Jasa Keuangan tidak dapat secara langsung mengawasi dan mengatur pinjaman online ilegal. Perlindungan hukum terhadap nasabah pengguna pinjaman online ilegal menurut peraturan POJK No.77/POJK.01/2016 dalam penyelenggaraannya tidak mengatur mengenai perlindungan hukum terhadap nasabah pinjaman online ilegal, hingga saat ini belum ada regulasi yang mengatur tentang perlindungan hukum nasabah pinjaman online ilegal maupun legal secara khusus.Kata kunci: Pinjaman Online ILegal, Perlindungan hukum, Otoritas Jasa Keuangan.